Disseminated Mycobacterium celatum disease with prolonged pulmonary involvement - Patsche, Cecilie Blenstrup; Svensson, Erik; Wejse, Christian (International journal of infectious diseases, 2014)
Mycobacterium celatum is a rare cause of human infection, causing disseminated disease in immunosuppressed individuals. Infections localized to the lungs and the lymph nodes have also been reported in immunocompetent individuals. The existing literature on the subject is limited as are experiences with treatment regimens and durations. In the case presented herein, two different treatment regimens were applied to an immunocompromised HIV-negative patient with primary skin involvement and extensive pulmonary involvement due to suspected relapse on isoniazid, ethambutol, and clarithromycin treatment. The treatment regimen was changed to azithromycin, ciprofloxacin, and pyrazinamide and the treatment duration was prolonged to a total of 24 months, with good effect.